2013
DOI: 10.3390/toxins5101814
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the Hyaluronic Acid Synthesis Inhibitor 4-Methylumbelliferone Suppresses SEB-Induced Lung Inflammation

Abstract: Exposure to bacterial superantigens, such as staphylococcal enterotoxin B (SEB), can lead to the induction of acute lung injury/acute respiratory distress syndrome (ALI/ARDS). To date, there are no known effective treatments for SEB-induced inflammation. In the current study we investigated the potential use of the hyaluronic acid synthase inhibitor 4-methylumbelliferone (4-MU) on staphylococcal enterotoxin B (SEB) induced acute lung inflammation. Culturing SEB-activated immune cells with 4-MU led to reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…4-MU suppresses staphylococcal enterotoxin B- [279] and LPS-induced lung inflammation [280]. 4-MU treatment in vivo protected against central nervous system autoimmunity and increased CXCL12 expression in the inflamed nervous system [281].…”
Section: Ha As Therapeuticmentioning
confidence: 99%
“…4-MU suppresses staphylococcal enterotoxin B- [279] and LPS-induced lung inflammation [280]. 4-MU treatment in vivo protected against central nervous system autoimmunity and increased CXCL12 expression in the inflamed nervous system [281].…”
Section: Ha As Therapeuticmentioning
confidence: 99%
“…Significantly increased HA production (by 32-fold in the circulation) has been found as a characteristic of patients with acute peripheral lung injury (20) and block HA production by hyaluronan synthase inhibitors effectively suppressed staphylococcal enterotoxin-induced inflammation (21). …”
Section: Introductionmentioning
confidence: 99%
“…Three different approaches using "novel inhibitor" [4], an FDA-approved drug [5], or intravenous immunoglobulin (IVIG) therapy [6] are presented, addressing the urgent need for developing therapeutics against staphylococcal superantigens.…”
mentioning
confidence: 99%
“…The article "Treatment with the hyaluronic acid synthesis inhibitor 4-methylumbelliferone suppresses SEB-induced lung inflammation" presents the use of 4-methylumbelliferone (4-MU), an inhibitor of hyaluronic acid (HA) synthesis, to diminish SEB-induced lung inflammation in vivo [4]. In vitro studies using mouse splenocytes showed 4-MU inhibits SEB-induced T cell apoptosis and downregulates cytokine expression.…”
mentioning
confidence: 99%